Are Patients Informed When They Consent to ERCP? - Sinead O’Sullivan; Craig Crippen; Terry Ponich (Canadian Journal of Gastroenterology)
BACKGROUD: Only the British Society of Gastroenterology has published consent guidelines that are inclusive for endoscopic retrograde cholangiopancreatography (ERCP). Previous research has shown that there are variations in the information discussed with patients who are undergoing ERCP.